Implementation of The Internet of Things for Public Street Light - atmi asri; Moh. Andika Pratama (BEST, 2022)
Currently, there are still many street lighting systems with electrical resources that use a full power system or a time system to regulate the power issued by the lamp so that in terms of the costs incurred for the lamp, it is also quite large. And in terms of maintenance, for now the problematic street lighting is still using conventional methods, namely waiting for damage reports from the field directly so that the handling of damaged lamps is very slow. Based on these problems, a street lighting lamp with automatic control will be designed that can adjust the light intensity and report the status of the lamp online through the Internet of Things (IoT) website which can be accessed using a smartphone or PC connected to the internet so that energy use and handling actions will be carried out. damage is more efficient. In this study, an automatic PJU was designed with a Passive Infrared Receiver (PIR) sensor to detect the presence or absence of objects around the lamp and an ESP module to connect the hardware to the internet network via a Wi-Fi connection . For the automatic system of turning on and off the lights based on bright and dark conditions of sunlight using a Photocell containing a Light Dependent Resistor (LDR) . With the use of this system, it can be proven that the use of Passive Infrared Receiver (PIR) sensors and Thingspeak website-based monitoring can streamline spending on electricity financing and accelerate the handling of lamp damage.